The Jewish press and the Holocaust, 1939 - 1945 : Palestine, Britain, the United States, and the Soviet Union - Gorni, Yosef 1933- (Cambridge Univ. Press, 2012)
Introduction: The transnational community -- I. From concern to outcry 1939-1942. Chapt. I. The Hebrew-language press in Palestine (Davar, Hatzofe, Ha'aretz, Haboqer, Hamashqif) -- Chapt. 2. Sounding the alarm: the American Jewish press, 1939-1942 -- II. The illusion dashed 1942-1945 -- Chapt. 3. The Hebrew-language press in Palestine -- Chapt. 4. The American Jewish press -- Chapt. 5. The British Jewish press, 1939-1945 -- Chapt. 6. The brief days of Jewish national unity: Aynikayt, 1942-1945 -- III. The individual confronts the horror -- Chapt. 7. Itzhak Gruenbaum: the main defendant -- Chapt. 8. The optimism that deludes the intellectuals -- Chapt. 9. Between Lidice and Majdanek -- Chapt. 10. Remarks on the continuing Jewish angst -- Chapt. 11. Conclusion